Effectiveness of Hypnosis in Combination with Conventional Techniques of Behavior Management in Anxiety/Pain Reduction during Dental Anesthetic Infiltration - A. Ramírez-Carrasco; C. Butrón-Téllez Girón; O. Sanchez-Armass; M. Pierdant-Pérez (Pain Research and Management)
Background and Objective. Anxiety/pain are experiences that make dental treatment difficult for children, especially during the time of anesthesia. Hypnosis is used in pediatric clinical situations to modify thinking, behavior, and perception as well as, recently, in dentistry; therefore the aim of this study was to evaluate the effectiveness of hypnosis combined with conventional behavior management techniques during infiltration anesthetic. Methods. Anxiety/pain were assessed with the FLACC scale during the anesthetic moment, as well as heart rate variability and skin conductance before and during the anesthetic moment, between the control and experimental group. Results. A marginal statistical difference (p=0.05) was found in the heart rate between baseline and anesthetic moment, being lower in the hypnosis group. No statistically significant differences were found with the FLACC scale or in the skin conductance (p>0.05). Conclusion. Hypnosis combined with conventional behavior management techniques decreases heart rate during anesthetic infiltration showing that there may be an improvement in anxiety/pain control through hypnotic therapy.